An investigation on the suitability of hydrated building lime from travertine limestone outcrop of Bogongo, South West of Cameroon. (December 2020) - Billong, Ndigui; Boubakar, Likiby; Bayiha, B.N.; Njimbouombouo, S.M.; Melo, Uphie C.; Oti, Jonathan; Kinuthia, John
Highlights: The limestone from the travertine contained about 94% CaCO3 . CL 90 S hydrated lime could be produced using the travertine of Bogongo. The Bogongo travertine limestone should be fired between 550 °C to 910 °C. The TiO2 content of the limestone could contribute to the yellowish color of the lime. Abstract: In the present study, physico-chemical investigations were carried out on hydrated lime produced from the limestone of the travertine outcrop of Bogongo in the South West Region of Cameroon. The aim was to evaluate the suitability of that hydrated lime as building lime. The raw material was characterized and then fired at 900 °C. The fired product was hydrated, dried and also characterized. Chemical and mineralogical analyses, density, BET specific surface measurements and thermal analyses were performed. Results were compared to those for an EN 459-1 CL 90-S industrial commercial hydrated lime. It has been shown that, hydrated lime production using the raw material from the Bogongo travertine could yield products with almost similar physico-chemical properties compared to imported CL 90 S hydrated lime, thus could have positive consequence in the commercial exploitation of the Bogongo travertine limestone outcrop.